The Role of Media Relations and Media Innovation of “Guns N Roses” Music Concert - Lailatul Fitroh; Susi Andrini (Ridwan Institute, 2022)
The scope of the research looks at the use of media relations at the Guns N Roses music concert with public relations media users in terms of event promotion implemented by Third Eye Management (TEM) as the event promoter. The success of the music concert event led to a search that was studied in terms of the use of media relations and media innovations applied by stakeholders as a media for event promotion. The purpose of this study was to identify and understand the role of media and media innovation at the Guns N Roses music concert event. The literature review used includes public relations, media relations, and media innovation. The research approach used in this research is descriptive-qualitative. Techniques in collecting data in this study used interviews and observation. The analysis technique applied through the Miles and Huberman interactive model, namely: (a) Data reduction level (b) Data presentation stage (c) Closing or reviewing phase. The results of the study indicate that there is a role for media innovation and media relations in the management of the Guns N Roses music concert event which is applied by TEM as the promoter of the event, which has a significant effect on the management of the event. This can be seen from the use of Instagram's new media as a new idea to provide services to the media and the community based on innovation and technology that can benefit various parties, both the media and the general public.